Rare presentation of foveal hypoplasia: A case report - Manandhar, Ashma (Journal of Chitwan Medical College, 2024)
Twenty-five years lady presented to retina outpatient department for routine check-up. She gave history decrease in vision both eyes since childhood. Her vision on examination was 2/60 in both eyes with no improvement with glasses. On examination there was nystagmus, anterior chamber depth, iris colour, lens and vitreous were normal. On fundus examination, optic disc, retinal vessels were normal. There was no foveal reflex and lattice degeneration was noticed superotemporally. Optical coherence tomography confirmed features of atypical foveal hypoplasia both eyes